Cyber Public Relations Communication Strategy In Maintaining The Image Of Malang City Government Post-Kanjuruhan Tragedy - Novi Ratriningtyas; Sukma, Ferry Indra; Ramadian, Vania Desty (oneamd.com, 2025)
The development of technology and the internet has transformed the communication landscape,including within the realm of government. Social media platforms like Instagram have becomeimportant tools for government agencies to interact with the public, disseminate information, andmanage their image. The Public Relations Office of Malang City Government utilizes the Instagramaccount @humaskotamalang as a Cyber Public Relations platform to manage communication inthe aftermath of the Kanjuruhan tragedy, which significantly impacted the local government'simage. The research object is the Public Relations Office of Malang City Government through theInstagram account @humaskotamalang, specifically in handling news coverage and responses tothe Kanjuruhan tragedy. The research method employs a qualitative approach with a case studymethod. Data was collected through observation of content on the @humaskotamalang Instagramaccount, in-depth interviews with two key informants (Head of Leadership Communication SubDivision and Instagram Account Manager), and documentation. Data analysis was conducted usingdata reduction, data display, and conclusion drawing techniques, utilizing the 7CS-PRcommunication strategy theoretical framework. The results indicate that the Public Relations Officeof Malang City Government has effectively implemented a Cyber Public Relations communicationstrategy through Instagram by applying the 7CS-PR approach. The uploaded content related tothe Kanjuruhan tragedy reflects the government's efforts to demonstrate concern, transparency,and commitment to resolving the case. In conclusion, the implementation of the 7CS-PR strategyproves effective in building credibility, relevant context, useful content, message clarity,communication consistency, appropriate channel selection, and adaptation to audience capability.